A hospital-based observational cohort study exploring pain and biomarkers in patients with hand osteoarthritis in Norway: The Nor-Hand protocol. Issue 9 (24th September 2017) - Gløersen, Marthe; Mulrooney, Elisabeth; Mathiessen, Alexander; Hammer, Hilde Berner; Slatkowsky-Christensen, Barbara; Faraj, Karwan; Isaksen, Thore; Neogi, Tuhina; Kvien, Tore K; Magnusson, Karin; Haugen, Ida Kristin
Abstract : Introduction: We have limited knowledge about the underlying disease mechanisms and causes of pain in hand osteoarthritis (OA). Consequently, no disease-modifying drug exists, and more knowledge about the pathogenesis of hand OA is needed, as well as a validation of different outcome measures. Our first aim of this study is to explore the validity of various imaging modalities for the assessment of hand OA. Second, we want to gain a better understanding of the disease processes, with a special focus on pain mechanisms. Methods and analysis: The Nor-Hand study is a hospital-based observational study including 300 patients with evidence of hand OA by ultrasound and/or clinical examination. The baseline examination consists of functional tests and joint assessment of the hands, medical assessment, pain sensitisation tests, ultrasound (hands, acromioclavicular joint, hips, knees and feet), CT and MRI of the dominant hand, conventional radiographs of the hands and feet, fluorescence optical imaging of the hands, collection of blood and urine samples as well as self-reported demographic factors and OA-related questionnaires. Two follow-up examinations are planned. Cross-sectional analyses will be used to investigate agreements and associations between different relevant measures at the baseline examination, whereas the longitudinal data will be used for evaluation of predictors for clinical outcomes. Ethics and dissemination: The protocol is approved by the Norwegian Regional Committee for Medical and Health Research Ethics (Ref. no: 2014/2057). The participants receive oral and written information about the project and sign a consent form before participation. They can, whenever they want, withdraw from the study, and all de-identified data will be safely stored on the research server at Diakonhjemmet Hospital. Results will be presented at international and national congresses and in peer-reviewed rheumatology journals. Trial registration number: NCT03083548; Pre-results.